Repurchases after being well known as good news - Lee, Inmoo; Park, Yuen Jung; Pearson, Neil D. (Journal of Corporate Finance, 2020)
Using recent U.S. data, we find that long-horizon abnormal returns following repurchase announcements made after 2001 are much lower than those following earlier announcements. The equity-linked compensation of senior management of buyback firms exceeds that of matching firms, especially for repurchases announced after 2001. Transient institutional investors equity holdings of buyback firms are smaller than their holdings of matching firms following buyback announcements by repeat repurchasers during 2002–2006. The results suggest that many recent buybacks have not been motivated by fundamentals-based factors such as undervaluation, and that non-fundamentals-based factors such as managerial self-interest have become more important.